Potential association of Trypanosoma cruzi DTUs TcV and TcVI with the digestive form of Chagas disease - Monje Rumi, Maria Mercedes (2020)
The relationship among genetic diversity of Trypanosoma cruzi and clinical forms of Chagas disease remain elusive. In order to assess the possible association between different T. cruzi Discrete Typing Units (DTUs) and the clinical pictures of the disease, 205 chronic patients from Salta province, Argentina, were analysed. One hundred and twenty-two of these patients were clinically categorized as: cardiac 38.5% (47/122), digestive 15% (18/122), cardio-digestive 16% (20/122) and asymptomatic 30% (37/122). From each patient, blood samples were taken for both, Polymerase Chain Reaction (PCR) targeting kDNA and blood culture analyses. The presence of T. cruzi kDNA was detected in 43% (88/205) of the patients. T. cruzi DTUs were identified in 74% (65/88) of the kDNA positive patients by PCR-hybridization using specific probes. We detected the presence of DTUs TcI, TcII, TcV and TcVI. Single infections (i.e. presence of only one DTU in the sample) were detected in 38.64% of the samples (34/88), while mixed infections were 35.23% (31/88). TcV was the most prevalent DTU (60.3%- 53/88). The association analyses showed, for the first time to the best of our knowledge, that TcV and TcVI were associated with the digestive form of Chagas Disease (Fisher p = .0001).